Technical and physical performances of Chinese Super League soccer players differ according to their playing status and position - Gai, Y.; Volossovitch, A.; Leicht, A. S.; Gómez, M. Á. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to compare the technical and physical performances of starters, substitutes and whole-match players of different playing positions: central defender, full-back, central midfielder, wide midfielder, and forward. Data were collected from the Chinese Super League. Technical and physical match-performances were analysed using independent / paired t-tests for the following groups: starters (n = 4,794) vs. substitutes (n = 1,208); whole-match players (n = 3,505) vs. substitutes (n = 1,208); within-player comparisons: starters (n = 258) vs. substitutes (n = 258). Significant differences were identified between substitutes and starters/whole-match players for central defenders (number of shots, total distance), central midfielders (high-intensity and total distance, number of high-intensity runs and sprints), wide-midfielders (high-intensity distance, number of high-intensity runs and sprints) and forwards (number of forward passes). Significant differences were identified during within-player comparisons for fullbacks (shot success, ground challenges success), central midfielders (number of passes, shots, aerial challenges and ground challenges), wide midfielders (number of high-intensity runs, sprint % of distance) and forwards (sprint % of distance, number of shots). Substitutes in the CSL experienced greater work-rates and completed more technical actions than starters or whole-match players but with a lower efficacy that was modulated by playing position.